Kirk-Othmer Encyclopedia of Chemical Technology 2003
DOI: 10.1002/0471238961.1921182206011818.a01.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching Agents

Abstract: A bleaching agent is a material that lightens or whitens a substrate through chemical reaction. The bleaching reactions usually involve oxidative or reductive processes that degrade color systems. These processes may involve the destruction or modification of chromophoric groups in the substrate as well as the degradation of color bodies into smaller, more soluble units that are more easily removed in the bleaching process. The most common bleaching agents generally fall into two categories: chlorine and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In addition, it was found that the slump values varied slightly between the control and other two chemicals used in PAC. Amongst the three oxidizing agents, the slump value for Ca(ClO) 2 was the lowest, followed by H 2 O 2 and H 2 O. e plastic aggregates undergo surface modification due to oxidation reaction with oxidizing agents, and Ca(ClO) 2 is the strongest oxidizing agent, followed by H 2 O 2 and H 2 O [16]. Treating the plastic with Ca(ClO) 2 may modify the initially smooth surface to be more angular and rougher, resulting in more contact and higher friction between the particles, therefore causing a lower slump and workability.…”
Section: Testing Methodsmentioning
confidence: 98%
“…In addition, it was found that the slump values varied slightly between the control and other two chemicals used in PAC. Amongst the three oxidizing agents, the slump value for Ca(ClO) 2 was the lowest, followed by H 2 O 2 and H 2 O. e plastic aggregates undergo surface modification due to oxidation reaction with oxidizing agents, and Ca(ClO) 2 is the strongest oxidizing agent, followed by H 2 O 2 and H 2 O [16]. Treating the plastic with Ca(ClO) 2 may modify the initially smooth surface to be more angular and rougher, resulting in more contact and higher friction between the particles, therefore causing a lower slump and workability.…”
Section: Testing Methodsmentioning
confidence: 98%
“…But for electrodepositing CdS as a wide-bandgap hole back diffusion barrier (hbdb) layer, precursors should be chosen very carefully because, in this case the whole glass/ FTO/p-window/CdTe absorber layer would require to be 1 3 submerged into the CdS electrolytic bath. Chlorine being a very strong corrosive agent and for having the strong hydrochloric acidity due to Cl − and H + ions in the electrolyte, the underlying device structure can be dissolved [21]. Therefore, cadmium acetate [Cd(CH 3 COO) 2 ] precursor with weaker acidity has been used in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Bleach stability is known to decrease at lower pH, and therefore, we hypothesized that the spontaneous pH shift could be associated with a loss of hypochlorite. Because of the potential for incomplete reaction conversion upon bleach decomposition, an experiment was designed to assess the oxidative potential of residual bleach in the reaction mixture at various time points.…”
Section: Epoxidation To Prepare Epoxyketonementioning
confidence: 69%